2014
DOI: 10.1002/jmv.23894
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus and Epstein–Barr virus DNA in Chinese children with tonsillar and/or adenoidal hypertrophy

Abstract: Tonsillar and adenoidal hypertrophy are prevalent otolaryngologic disorders in children, but their pathogenesis is largely unknown. The presence of human papillomavirus (HPV) and Epstein-Barr virus (EBV) DNA in 146 tonsil and/or adenoid tissue specimens from 104 Chinese children with tonsillar and/or adenoidal hypertrophy were screened using flow-through hybridization gene-chip technology and real-time fluorescence-based quantitative PCR. Then, the relationships between the prevalence of the viruses and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 18 publications
6
16
0
1
Order By: Relevance
“…Here, an EBV DNA prevalence in tonsil brushings of 74.4% in adults is reported, consistent with the previously observed prevalence of 66% to 71% in adult's tonsil tissue . EBV prevalence among children in this study (40.6%) is in line with a reported prevalence of 43% to 50% in children in some, but not all other studies (29%‐80%; see Table ). The higher prevalence in tonsils of adults compared with children agreed with other studies evaluating tonsillar specimens .…”
Section: Discussionsupporting
confidence: 92%
“…Here, an EBV DNA prevalence in tonsil brushings of 74.4% in adults is reported, consistent with the previously observed prevalence of 66% to 71% in adult's tonsil tissue . EBV prevalence among children in this study (40.6%) is in line with a reported prevalence of 43% to 50% in children in some, but not all other studies (29%‐80%; see Table ). The higher prevalence in tonsils of adults compared with children agreed with other studies evaluating tonsillar specimens .…”
Section: Discussionsupporting
confidence: 92%
“…First, we did not evaluate the status of EBV infection in the adenoids and tonsils of healthy control subjects. Although some authors have suggested that EBV could be involved in recurrent tonsillitis and adenotonsillar hyperplasia, this has not been confirmed by subsequent studies. In our study, the prevalence of EBV DNA was high in the adenoids of the adults with chronic tonsillitis and focal tonsils, but their adenoids did not have recurrent inflammation or hyperplasia.…”
Section: Discussionmentioning
confidence: 84%
“…However, many viruses are detected in tonsillar and adenoid tissues recently [1]. Despite these findings, systematic studies of viruses in adenoids and tonsils have been rare, especially in recurrent and/or hypertrophic adenotonsillar diseases.…”
Section: Introductionmentioning
confidence: 93%
“…Recurrent and chronic diseases of tonsils and adenoids are highly frequent in children and lead to chronic activation of the immune response, resulting in hypertrophy of the adenoidal and tonsillar lymphoid tissues [1]. These reactions can adversely affect a child, especially when there is hypertrophy and/or recurrent infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation